The Effectiveness of Nineteen's RAPCOV Screening Education Through Character Health Communication on Knowledge of Covid-19 Infection - Siti Noorbaya; Dwi Riyan Ariestantia; Fauziah Fauziah (Comment: an International Journal of Community Development, 2021)
The study "Educational Effectiveness of the Nineteen RAPCOV Screening Against Knowledge of Covid 19 Infection" is a research on the development of a health promotion program designed to provide information and education to the public. Rapid tests are part of the initial screening for Covid 19. However, there are still many people who do not understand about Covid 19 infection and lack of knowledge about the benefits and objectives of rapid tests. It is undeniable that when a rapid test is carried out, there will be rejection from the community, this is still a lack of education or socialization and clear information. In addition, some people assume that everyone who has a Reactive rapid test result is definitely positive for Covid 19. As health workers and educators in the Front Guard, they must have good communication skills and be able to take a character-based persuasive approach. The purpose of this study was to determine the effect of RAPCOV Nineteen Screening Education on public knowledge of Covid 19 infection in the working area of ​​the South Sempaja Health Center. In this study, the method used was pre-experimental with a posttest only control group design. The population in this study was 370 people, with a sample of 34 people selected based on cluster random sampling. The results of this study are knowledge about Covid 19 infection before being given RAPCOV Nineteen Screening Education which is classified as good by 32.4% and after being given RAPCOV Nineteen Screening education there is an increase in knowledge of 97.1%. There is a significant effect of RAPCOV Nineteen Screening Education on knowledge of Covid 19 infection before and after the intervention with p value = 0.555 (α > 0.05)